2020
DOI: 10.1029/2020jd032695
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Upper Tropospheric Water Vapor Monthly Variation in Reanalyses With Near‐Global Homogenized 6.5‐μm Radiances From Geostationary Satellites

Abstract: The monthly variation of upper tropospheric water vapor (UTWV) simulated by six reanalysis data sets is evaluated with homogenized water vapor radiance observations from international geostationary (GEO) weather satellites by using a profile-to-radiance approach over 45°N to 45°S regions for the period 2015-2017. Results show that reanalysis data sets have an overall good agreement with observations. However, a widespread wet bias is found in all reanalyses and is more dominant in large-scale subsidence region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Xue et al. (2020) found a wet bias with respect to satellite observations in the free troposphere, which is most pronounced in regions of large‐scale subsidence. Nevertheless, the data set provides a valuable constraint of the humidity distribution and can be used to estimate its natural variability.…”
Section: Dyamond Simulationsmentioning
confidence: 99%
“…Xue et al. (2020) found a wet bias with respect to satellite observations in the free troposphere, which is most pronounced in regions of large‐scale subsidence. Nevertheless, the data set provides a valuable constraint of the humidity distribution and can be used to estimate its natural variability.…”
Section: Dyamond Simulationsmentioning
confidence: 99%
“…It should be pointed out that potential biases with respect to observations exist in the ERA5 water vapor fields. Xue et al (2020) found a wet bias with respect to satellite observations in the free troposphere, which is most pronounced in regions of large-scale subsidence. Nevertheless, the data set provides a valuable constraint of the humidity distribution and can be used to estimate its natural variability.…”
Section: Post-processing and Profile Selectionmentioning
confidence: 69%
“…The spatial variations in radiances or BT measurements from AHI water vapor absorption bands can be interpreted as changes in moisture averaged from different atmospheric layers, which are nearly proportional to the natural logarithm of the humidity changes. This radiance-humidity relationship has been illustrated in many studies (Iacono et al, 2003;Soden & Bretherton, 1993;Xue et al, 2020), which found that this simple radiance-humidity relationship explains greater than 90% of the variances in BT for water vapor bands. For Band 8 (centered at 6.28 μm), a 2 K decrease in BT corresponds to a water vapor increase of ∼30% (∼40%) around 350 hPa for a summer (winter) profile.…”
Section: Methodologiesmentioning
confidence: 75%